2000
DOI: 10.1007/s002610000004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crohn disease activity with magnetic resonance imaging

Abstract: An excellent statistical correlation was found between biologically "active" disease and the following MRI parameters: wall gadolinium enhancement, wall hyperintensity on T2-weighted fat-suppressed images, and hyperintensity of fibrofatty proliferation on T2-weighted fat-suppressed images. Therefore, MRI can be valuable in assessing CD activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
129
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(145 citation statements)
references
References 32 publications
9
129
1
6
Order By: Relevance
“…Maccioni et al [33] reported a significant correlation between MR signs of intestinal inflammation (oedema in the perienteric fat, wall thickening, contrast enhancement) with a biological activity score which included white blood cells, orosomucoid levels and CRP in 20 CD patients. These results were not confirmed by other authors [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Maccioni et al [33] reported a significant correlation between MR signs of intestinal inflammation (oedema in the perienteric fat, wall thickening, contrast enhancement) with a biological activity score which included white blood cells, orosomucoid levels and CRP in 20 CD patients. These results were not confirmed by other authors [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In der Submukosa kommt es zu Fettgewebseinlagerungen, was zu einer Schichtung in den T2-gewichteten Sequenzen führt. Fettunterdrückte Sequenzen füh-ren zu einer Signalminderung und damit zu einer Differenzierung zu einem akuten Ödem [14,16]. Befunde bei Colitis ulcerosa…”
Section: Reparativer/regenerativer Subtypunclassified
“…Like CT enterography, MRE involves the use of an oral contrast medium to distend the intestinal loops. Unlike CTE, it also requires the administration of drugs like butylbromide that reduce intestinal peristalsis, a source of motion artifacts that can diminish image quality [56].…”
Section: Magnetic Resonancementioning
confidence: 99%